(untitled) (Interdisciplinary Studies Journal, 2021)
This article aims to identify whether the fundamental rights of the elderly are respected by long-term care institutions. It was necessary to understand the historical process of the conquest of the rights of the elderly, identify the legislation and the agencies and entities that are part of the protection network. The researchers used the deductive method of problem analysis, considering the national and local contexts, in this order of reasoning, analyzing the legislation of protection agencies and entities, then conducting a technical visit to a long-term care institution located in São Borja (RS), the São Vicente de Paula Asylum. At the Asylum, which still uses the term "asylum," they interviewed the responsible social worker to check whether the fundamental rights provided in the Elderly Statute and the National Policy for the Elderly (PNI) are guaranteed. Subsequently, they addressed issues related to basic institutional demands, as well as family abandonment within the researched institution.